Camino a Tondo : un cuento del pueblo Unkundo del Zaire - Aardema, Verna; Hillenbrand, Will.; Zubizarreta, Rosa (Rosalma) (New York : Scholastic, 1995)
On his way to his wedding, with his friends as attendants, a civet cat meets with extraordinary and unexpected delays.
Translation of: Traveling to Tondo; a tale of the Nkundo of Zaire.
Keywords: Folklore -- Congo (Democratic Republic)